Metabolomic Profile in the Aqueous Humor of Congenital Ectopia Lentis. (4th March 2023) - Liu, Liyan; Li, Yiqing; Guo, Dongwei; Ye, Huiwen; Qi, Haotian; Zou, Bin; Zheng, Danying; Jin, Guangming
Abstract: Purpose: To explore the metabolic profiles in the aqueous humor (AH) of patients with congenital ectopia lentis (CEL). Methods: We conducted a comprehensive analysis of the metabolites of AH samples of patients with CEL ( n = 22) and age-matched patients ( n = 22) with congenital cataract by ultra-high performance liquid chromatography tandem-mass spectrometry. The metabolomic characteristics were visualized by principal component analysis, orthogonal partial least squares discriminant analysis and heat map. The levels of the differential metabolites were also compared between CEL patients with and without FBN1 mutations. Pathway enrichment analysis was performed by using Kyoto Encyclopedia of Genes and Genomes. Receiver operating characteristic analysis was performed to select potential biomarkers. Results: There were 175 differential metabolites identified between the two groups. Eight metabolites were found to be potential biomarkers in AH of CEL patients. The CEL group showed a significant increase in α-ketoglutarate and decrease in citrate, suggesting that the tricarboxylic acid (TCA) cycle was disturbed. l -proline, prolyl-hydroxyproline, and l -histidine were reduced, which prompted enhanced degradation of microfibrils and collagen. Insidious retinal nerve damage was implied because N-Acetyl-aspartylglutamic acid and N-Acetyl-l -aspartic acid were found to be significantly increased. Pathway enrichment analysis indicated that disturbances in amino acid metabolism and carbohydrate metabolism were the key processes in the pathogenesis of CEL and that TCA cycle disorder may be the driving force behind disease occurrence. Conclusion: These data reveal the characteristics in the metabolomic profiles of the AH of CEL patients, which help provide insights into the pathogenesis of this rare disease.